Correction: Obesity-related indicators and tuberculosis: A Mendelian randomization study. - Nuannuan Cai; Weiyan Luo; Lili Ding; Lijin Chen; Yuanjiang Huang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297905.].